IMPLEMENTASI SIFAT TA’AWUN DALAM LEMBAGA KEUANGAN SYARIAH MELALUI AKAD Al –QARDH - Rukiah, Rukiah (Studi Multidisipliner: Jurnal Kajian Keislaman, 2019)
The purpose this paper were to find out the concept of Al-qardh in Islamic financial institutions from a review of fiqh, what are the obstacles of implementation in the field, and what products use this contract in financial institutions. The analytical method used is a literature review and findings in the field. The results found were qardh contract in practice, it was not maximally utilized by financial institutions to optimize their social functions, and the lack of awareness of customers to return qardh debt, because there was a customer's perception that the qardh debt was a virtue fund.